Cytomegalovirus infection post‐pancreas–kidney transplantation – results of antiviral prophylaxis in high‐risk patients. (3rd June 2013) - Fallatah, Samira M.; Marquez, Max A.; Bazerbachi, Fateh; Schiff, Jeffrey R.; Cattral, Mark S.; McGilvray, Ian D.; Norgate, Andrea; Selzner, Markus; Rotstein, Coleman; Husain, Shahid
Abstract Background Cytomegalovirus (CMV) is a major pathogen affecting solid organ transplant (SOT) recipients. Prophylactic strategies have decreased the rate of CMV infection/disease among SOT. However, data on the effect of current prophylactic strategies for simultaneous pancreas–kidney (SPK) or pancreas after kidney (PAK) transplant remain limited. We report our experience of CMV prophylaxis in SPK/PAK recipients. Methods A total of 130 post‐SPK/PAK patients were analyzed retrospectively for the rate of CMV and the risk factors associated with the acquisition of CMV. All patients received antiviral prophylaxis. The follow‐up period was one yr post‐transplant or until death. Results The rate of CMV post‐SPK/PAK transplant was 24%, 44%, and 8.2% among the whole cohort, the D+/R− and the R+ groups, respectively. Median time of prophylaxis was 49 (0–254) d. In the whole cohort, risk factors for CMV infection/diseases were D+/R− CMV status (odds ratio [OR] = 16.075), preceding non‐CMV (infection caused by bacteria or fungi and other viruses) infection (OR = 6.362) and the duration of prophylaxis (OR = 0.984). Among the CMV D+/R− group, non‐CMV infection was the only risk factor for CMV disease (OR = 10.7). Conclusions Forty‐four per cent (25/57) of the D+/R− recipients developed CMV infection/disease despite CMV prophylaxis. Current CMV prophylaxis failed to prevent CMV infection/disease in this group of patients.